Malignant melanoma and 18F-FDG-PET: Should the whole body scan include the legs? - Löffler, M.; Weckesser, M.; Franzius, Ch.; Nashan, D.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: 18F-FDG-PET (FDG-PET) is established in staging and follow-up of malignant melanoma. The legs are affected in 10-40% at time of diagnosis even if the primary is at the arms and torso. Imaging including the legs may detect distant manifestations but increases duration of the scan by ~30 min. We intended to disclose the diagnostic benefit of scanning the legs and to evaluate the therapeutic benefit resulting. Patients, Methods: In this retrospective analyse 213 consecutive PET studies of 153 patients with suspected or recent malignant melanoma were re-evaluated for metastastic spread by a blinded investigator. Histopathological follow-up was assessed for confirmation. Results: Suspicious findings at the legs were depicted in 53 patients on 76 occasions. 38/53 showed pathologic uptake in the torso as well. In 15/53 patients it was restricted to the legs. One of them had a hitherto unknown, clinically relevant finding that was not apparent in palpation and inspection. In 6 other patients with primary location at the legs a validation of the positive PET findings was not possible up to now. Conclusion: Metastases and local recurrence of malignant melanoma at the legs were found in 41% of women and 27% of men. However, a long scan does not yield relevant additional data. We found isolated new manifestations at the legs in only 1/153 patients. We recommend performing a long scan only in patients with previous melanoma manifestations restricted to the legs. In all other cases a short scan of the torso and proximal thighs is sufficient. This allows a higher number of PET-scans without loss of diagnostic power and a shorter examination time.
Keywords: Malignant melanoma; FDG-PET; ganglion; dermatofibroma